AČ = AB
AČ  BČ = AB  BČ
(A + B)(A  B) = B(A  B)
A + B = B
B + B = B
2B = B
2 = 1
OK, I'll try doing it with numbers
A = B = 1
AČ = AB => 1*1 = 1*1 => 1
AČ  BČ = AB  BČ => 1  1 = 11 => 0
(A + B)(A  B) = B(A  B) = (1+1)(11) = 1(11) =>true 0=0!!! (sure enough!)
1+1 = 1 False...
OK, now I'll try with a different number
A = B = 2
AČ = AB => 2*2 = 2*2 => 4
AČ  BČ = AB  BČ => 4  4 = 44
(A + B)(A  B) = B(A  B) = (2+2)(22) = 2(22) =>True
(2+2)(22)=>2*2 + 2*2 2*2  2*2 = 0
2(2*2) = 44 = 0
2+2 = 2 False...
Like I said...
Quote:
The fairytale maths starts here...
AČ  BČ = AB  BČ
since A = B all that = 0
2b = b => 2*0 = 0...

The line (A + B)(A  B) = B(A  B) only works because both sides are equal(and equal to zero).
taking it past that is impossible...
therefore the solution only has real answers if A and B = 0
the maths is fine, and can be solved, but like I said, it only has 1 possible real solution.
there are no imaginary solutions either, I just tried...
__________________